The Power Of The Acehnese Dinar And Dirham In Muamalah Transactions - Hadi Arifin; Damanhur Damanhur; Anwar Puteh; Yulius Dharma (LPPM, 2022)
Dinars and dirhams, have been used by the population since thousands of years ago, which are known as the essential medium of exchange (thaman haqiqi or thaman khalqi). Islam has introduced the dinar and dirham as currency. Dirham, for the first time used in Aceh during the Samudera-Pasai kingdom, which was then followed by the Aceh Darussalam kingdom and subsequently the use of the gold currency, expanded throughout the archipelago. Dirham, which means money made of silver. But in Samudera-Pasai, dirham means money made of gold. This gold coin weighs 0.57 grams, 18 carat quality with a diameter of one centimeter. Dinar and Dirham in the true sense, namely the dinar is made of 22 carat gold 4.25 grams, and the dirham is made of pure silver 2.975 grams.Based on UUPA No. 11 of 2006, the Aceh government has the authority to set requirements for bank financial institutions and non-bank financial institutions, and the Aceh government can explore gold mines in the Leuser Ecosystem (KEL) for the need to innovate various types of gold currency and gold jewelry that can prosper, can establish dinar-dirham financial institution, making dinar-dirham money, creating e-dinar-dirham, Dinar-DirhamCard, utilizing the Dinar-Dirham as the basis for the Mobil Payment System (MPS); innovating the birth of various currencies for the cyber age under the names Mondex, E-Cash, DigiCash, CyberCash, GoldCash, E-Gold and E-Dinar, E-Dirham, by establishing a Qanun, aiming to invest in the future development of aceh. The institution was given the task of creating dinars, which were kept, monitored, and exchanged. This financial institution in the long term; can be used for safe financial planning, used for children's education funds, family health funds, retirement preparation, and other activities. Meanwhile, physically, the dirham can be used for savings, investment, muamalah, and even zakat, infaq and diyat